Blended Formula Four Di (4D) with Actor Network Theory to Increases the Outcome of Literacy Culture - Tri Wahyu Liswati (IJORER : International Journal of Recent Educational Research, 2020)
The purpose of this research is to evaluate the effectiveness of the Blended Formula Four Di (4D) with Actor Network Theory in increasing the outcome of literacy culture is a case study that involves all school members. The obtained data were analysed by using qualitative descriptive methods. The analysis results inform that the Blended Formula Four Di (4D) with Actor Network Theory has proven to be effective in improving the outcome of literacy culture in schools. The application of "Blended Formula Four Di (4D) with Actor Network Theory to Increases The Outcome of Literacy Culture" is also able to improve literacy culture in SMAN 1 Ngimbang with indicators (1) increasing the number of visitors and borrowers in the library, (2) increasing the writing of the school residents, and (3) becoming the winner of the library competition.